2011
DOI: 10.1111/j.1365-2664.2011.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reflex indicators for measuring vitality and predicting the delayed mortality of wild coho salmon bycatch released from fishing gears

Abstract: Summary1. Effective management of fish and wildlife populations benefits from an understanding of the effects of stressors on individual physiology. While physiological knowledge can provide a mechanistic understanding of organismal responses, its applied utility is limited because it cannot easily be used by stakeholders. 2. Reflex action mortality predictors (RAMP) is a method that involves checking for the presence or absence of natural animal reflexes to generate a condition (RAMP) score in response to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(201 citation statements)
references
References 35 publications
6
192
2
1
Order By: Relevance
“…A more recent radio-tracking study has shown that endangered interior Fraser coho salmon released from a beach seine are more likely to reach their natal spawning areas with a better RAMP score (i.e. fewer impaired reflexes; [36]). Presumably by integrating underlying physiological systems, greater reflex impairment reflects a state further from homeostasis, from which a complete recovery is less likely and latent mortality is more likely.…”
mentioning
confidence: 99%
“…A more recent radio-tracking study has shown that endangered interior Fraser coho salmon released from a beach seine are more likely to reach their natal spawning areas with a better RAMP score (i.e. fewer impaired reflexes; [36]). Presumably by integrating underlying physiological systems, greater reflex impairment reflects a state further from homeostasis, from which a complete recovery is less likely and latent mortality is more likely.…”
mentioning
confidence: 99%
“…Conversely, declines of 6 and 8°C caused rapid equilibrium loss and significant reflex impairment, particularly at 8°C below ambient temperature. Equilibrium loss is a common result of cold shock exposure in fish, and is an indication of physiological stress that may lead to mortality (Griffith 1978, HyvĂ€rinen et al 2004, Donaldson et al 2008, Davis 2010, Raby et al 2012. Loss of ability to swim upright also greatly reduces the capacity of fish to move into deeper water to escape further cold exposure (in the case of storm-induced perturbation of shallow waters) or avoid predators, further increasing the probability of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5 RAMP indices were used: tail grab, body flex, head complex, vestibular−ocular response (VOR), and equilibrium. These metrics were chosen because they are strong indicators of vitality in other fish species in the context of fisheries-related stress (Raby et al 2012, Brownscombe et al 2013, as well as cold shock (Szekeres et al 2014). Tail grab was assessed by grabbing the fish's tail by hand, and was considered impaired if the fish did not immediately attempt to swim away.…”
Section: Cold Shockmentioning
confidence: 99%
“…This is the first step in developing a tagging system that can be used to test post-release behaviour and potentially physiological response to capture, handling and release (e.g. [39][40][41]). Therefore, we tagged five shortnose sturgeons with high-frequency accelerometers mounted on PSATs that recorded environmental variables over a 2-day period.…”
Section: Open Accessmentioning
confidence: 99%
“…High VeDBA during tag-load-related movements, indicated by high roll angles in the smallest individual, likely contributed to additional energy expenditure. The extended resting period and increased energy expenditure due to postrelease stress could contribute to increased vulnerability to other stressors, fishing recapture or death [30,31,40,41,59,[62][63][64][65].…”
Section: Post-release Behaviourmentioning
confidence: 99%